A workable tool for assessing eco-efficiency in dairy processing using process simulation. (1st November 2019) - Benoit, S.; Margni, M.; Bouchard, C.; Pouliot, Y.
Abstract: Process simulation (PS) is essential in the eco-efficiency assessments (EEA) of dairy processes. PS indeed allows for analysis of a process with the help of mathematical models, and its ability to calculate rapidly and at little cost the mass and energy balances of processes can be exploited in the EEA of dairy processes. This paper presents the prototype of a workable tool developed to carry-out EEA of dairy processes. A process modelling and simulation software dedicated to dairy processing was developed to perform inventories of material and energy flows (IMEF) on the processes modelled by the software user. Addition of impact analysis data sets allowed for quantification of the potential environmental impacts associated with the modelled processes. Inputting economic data then made it possible to calculate the economic value associated with the modelled processes. Gathering these methods within a single numerical tool enabled EEA of any process modelled by the software user, but also identification of the hot spots and the opportunities for eco-efficiency improvements, comparisons of several scenarios of raw milk valuation, and assessment of their economic viability. In order to present the operational aspect of the developed prototype, it was used to compare the EE of fluid milk processing in Canada (Quebec) and the United-States of America. Individual eco-efficiency indicators (EEI) results showed that the potential environmental impacts were higher for the American scenario in three damage categories out of four. Economic viability results showed a slight advantage for the American scenario. Considering all the EEI, the comparative EEA did not offer evidence of a general benefit of one scenario over the other. Graphical abstract: Image 107496 Highlights: Process simulation can make eco-efficiency assessments easier and faster. A numerical tool for eco-efficiency assessment in dairy processing was developed. Such tool allows for identification of hot spots and opportunities for improvements. Eco-efficiency of all raw milk valuation scenarios can be compared in this way. Profitability and rentability threshold of modelled processes can also be assessed.